Strategi produksi bunyi vokal oleh ventrilokuis Indonesia - Kustiawan, Roni; Indrayani, Lia Maulia; Ratnasari, Dewi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Ventriloquism or voice magic illusion involves the ability of speakers to control lip and jaw movements to create the impression that sound or speech comes from a puppet being played. This study aims to analyze the strategies used by ventriloquists in producing vowel sounds in Indonesian using the acoustic analysis method (spectrography). Our research data was obtained from three Indonesian ventriloquists who appeared in a video entitled "Moveless Lips Ventriloquism Tutorial (Indonesian Ventriloquist)" on Tenggo Wicaksono's Youtube channel. The data was analyzed using Praat software version 6.2.10 and adopting Instituut voor Perceptie Onderzoek (IPO) design stages. From the analysis of formant 1 and formant 2 on the spectrogram, the three ventriloquists in this study used the same strategy in producing vowel sounds, namely by lowering the tongue position compared to when speaking normally, except for the [a] sound, which requires a higher tongue position. However, regarding horizontal tongue movement, each respondent has a different strategy. Some change the tongue's position forward, while others do it the other way around.